2015
DOI: 10.1155/2015/529256
|View full text |Cite
|
Sign up to set email alerts
|

Model of Multilayer Knowledge Diffusion for Competence Development in an Organization

Abstract: Growing role of intellectual capital within organizations is affecting new strategies related to knowledge management and competence development. Among different aspects related to this field, knowledge diffusion has become one of interesting areas from both practitioner and researcher's perspective. Several models were proposed with main goal to simulate diffusion and to explain the nature of these processes. Existing models are focused on knowledge diffusion and they assume diffusion within a single layer us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…In terms of literature content, flipped classroom research involves theoretical research on its origin, definition, characteristics, local applicability of teaching mode, and construction of teaching mode, as well as practical research on teaching design combined with subject application and application effect detection. e applied research fields involve five levels: primary school, junior high school, senior high school, vocational college, and university, among which the flipped classroom teaching model is mostly applied in universities [7,8]. Based on the differences between Chinese and American cultures, this paper discusses how to localize the advantages of flipped classroom [9].…”
Section: Related Workmentioning
confidence: 99%
“…In terms of literature content, flipped classroom research involves theoretical research on its origin, definition, characteristics, local applicability of teaching mode, and construction of teaching mode, as well as practical research on teaching design combined with subject application and application effect detection. e applied research fields involve five levels: primary school, junior high school, senior high school, vocational college, and university, among which the flipped classroom teaching model is mostly applied in universities [7,8]. Based on the differences between Chinese and American cultures, this paper discusses how to localize the advantages of flipped classroom [9].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, virtual worlds have been used as laboratories and experimental platforms for studying economic behaviour and decision-making, areas such as the spread of virtual goods within virtual worlds (Bakshy, Karrer, and Adamic 2009;Huffaker et al 2011), labour markets (Horton, Rand, and Zeckhauser 2011), moral hazard (Tolvanen 2016), trust (Fiedler and Haruvy 2009;Fiedler, Haruvy, and Li 2011), avatar markets (Castronova 2001), and market efficiency (Golde 2008). A wide area of research based on a content within virtual worlds and online social networks is related to education (Baker, Wentz, and Woods 2009;Warburton 2009), collaborative learning (Lytras et al 2015;Różewski et al 2015) with special focus on dynamic experience management (Riedl et al 2008), interactions (Petrakou 2010), engagement , knowledge acquisition (Jankowski et al 2015), multilayer knowledge diffusion (Rożewski and Jankowski 2015), social learning innovations (Lytras et al 2014), web-based knowledge exchange (Filipowski et al 2012), and online marketplace (D'Avanzo and Kuflik 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tere are a lot of researchers who have studied this in depth; for example, Cao et al [9] took the forgetting mechanism into account and developed a completely new model. Rozewski and Jankowski [10] integrated self-learning ability into the model and simulated it with a new method. Furthermore, Wang et al found in the course of their research that human selflearning ability can spread knowledge more widely [11].…”
Section: Introductionmentioning
confidence: 99%